Dinâmica folicular ovariana comparativa entre as espécies bovina e equina - Oliveira, Andreza Pimenta de [UNESP]; Oliveira Filho, José Paes de [UNESP]; Meira, Cesinande de [UNESP] (My University, 2010)
The bovine estrous cycle is characterized by two or three waves of follicular development and each wave results in a follicle of pre-ovulatory diameter. The types of follicular waves in mares are major waves (characterized by dominant and subordinate follicles) and minor waves (largest follicle does not attain the diameter of a dominant follicle). In both species, the emergence of a follicular wave is stimulated by a FSH surge. This surge reaches a peak when follicles attain 4 mm in diameter in cattle and 13 mm in mare. Some days after the peak of the FSH surge and the emergence of the wave the follicles begin to undergo deviation. In this moment, the two largest follicles attain about 8.5 and 7.7 mm in diameter in cattle and 22 and 19mm in mare. The deviation is characterized by continued growth of the largest follicle to become the dominant follicle and reduced or terminated growth of the remaining follicles to become subordinate follicles. The two largest follicles grow in parallel until deviation and the future dominant follicle emerges approximately 6 h in cattle and 24 h in mares before the second largest follicle. Probably, this is enough time for the largest follicle to establish the deviation process before the second largest follicle reaches a similar diameter. The largest follicle suppresses circulating FSH concentrations to below the requirements of the smaller follicles, which causes their regression. The follicle produced FSH suppressants appear to be estradiol and inhibin. Besides FSH suppressing ability the largest follicle also develops the ability to utilize the reduced concentrations of FSH for its continued growth. There are elevated concentrations of circulating LH at the moment the deviation in both species and the activity of IGF-1 increases rapidly in the dominant follicle.

O ciclo estral bovino é caracterizado por duas ou três ondas de crescimento folicular e cada onda resulta em um folículo de diâmetro pré-ovulatório. Os tipos de ondas foliculares em éguas são ondas maiores (caracterizadas por folículos dominantes e subordinados) e ondas menores (o maior folículo não atinge o diâmetro de um folículo dominante). Em ambas espécies, a emergência de uma onda folicular é estimulada por uma onda de FSH. Esta onda alcança um pico quando os folículos atingem 4 mm em diâmetro na vaca e 13 mm na égua. Alguns dias depois do pico de FSH e da emergência da onda folicular, os folículos começam a sofrer o desvio. Neste momento, os dois maiores folículos atingem cerca de 8,5 e 7,7 mm em diâmetro na vaca e 22 e 19 mm na égua. O desvio é caracterizado pelo crescimento contínuo do maior folículo tornando-se o folículo dominante e pela redução ou interrupção do crescimento dos folículos remanescentes tornando-se folículos subordinados. Os dois maiores folículos crescem paralelamente até o desvio e o futuro folículo dominante emerge aproximadamente 6h na vaca e 24h na égua antes que o segundo maior folículo. Provavelmente, este é o tempo suficiente para o maior folículo estabelecer o processo de desvio antes que o segundo maior folículo atinja um diâmetro similar. O maior folículo suprime a concentração de FSH na circulação abaixo da necessidade dos folículos menores, o que provoca a regressão destes. Os fatores do folículo inibidores da produção de FSH parecem ser estradiol e inibina. Além da habilidade de suprimir o FSH o maior folículo também desenvolve a habilidade de utilizar reduzidas concentrações de FSH para continuar seu crescimento. Há uma concentração elevada de LH circulante no momento do desvio em ambas espécies e a atividade de IGF-1 aumenta rapidamente no folículo dominante.
Ovarian follicular dynamics: comparative study among cattle and equine species
Keywords: Cattle; Equine; Follicular deviation; Follicular wave; Bovino; Equino; Desvio Folicular; Onda Folicular